The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.31234/osf.io/sde3g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sufficient Reliability of the Behavioral and Computational Read-Outs of a Probabilistic Reversal Learning Task

Abstract: Task-based measures that capture neurocognitive processes can help bridge the gap between brain and behavior. To transfer tasks to clinical application, reliability is a crucial benchmark because it poses an upper bound to potential correlations with other variables (e.g., symptom or brain data). However, the reliability of many task-readouts is low. In this study, we scrutinized the re-test reliability of a probabilistic reversal learning task (PRLT) that is frequently used to characterize cognitive flexibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…There are multiple factors that may have contributed to these findings. Firstly, these complex measures are interactions between multiple noisy task measures, which is known to lead to a larger overall measurement noise 50,51 . Secondly, we found that multiple model-derived predictors showed a high degree of co-linearity and thus directly affected how well the impact of these metrics could be measured when used in the same model (cf.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple factors that may have contributed to these findings. Firstly, these complex measures are interactions between multiple noisy task measures, which is known to lead to a larger overall measurement noise 50,51 . Secondly, we found that multiple model-derived predictors showed a high degree of co-linearity and thus directly affected how well the impact of these metrics could be measured when used in the same model (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, parameter generalizability is naturally bounded by parameter reliability, i.e., the stability of parameter estimates when participants perform the same task twice (test-retest reliability) or when estimating parameters from different subsets of the same dataset (split-half reliability). The reliability of RL models has recently become the focus of several parallel investigations [46, 47, 71, 48], some employing very similar tasks to ours [72]. The investigations collectively suggest that excellent reliability can often be achieved with the right methods, most notably by using hierarchical model fitting.…”
Section: Appendix 2-tablementioning
confidence: 82%
“…Lastly, model parameter reliability might play a crucial role for our results: If parameters lack consistency between two instantiations of the same task (reliability), generalization between different tasks would necessarily be low as well. A recent wave of research, however, has convincingly demonstrated that good reliability is possible for several common RL models [47, 71, 48, 72], and we employ the recommended methods here [61, 53]. In addition, our simulation analysis shows that our approach can detect generalization.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…approach in which sessions are modeled jointly. The latter has recently been shown to yield superior reliability estimates in theory and practice in other cognitive tasks (for details, see below; Brown, 2020;Haines, 2021;Waltmann et al, 2021).…”
Section: Methodsmentioning
confidence: 99%